Adiponectin, leptin, nitric oxide, and C-reactive protein levels in kidney transplant recipients: comparison with the hemodialysis and chronic renal failure. (25th November 2016) - Ocak, Nihal; Dirican, Melahat; Ersoy, Alparslan; Sarandol, Emre
Abstract: Background: Cardiovascular disease (CVD) is the leading cause of mortality and morbidity in patients with chronic kidney disease (CKD) including kidney transplant recipients (KTR). Secondary lipid metabolism disorders, endothelial dysfunction, and inflammation enhance the risk of CVD development in these patients. The aim of the present study was to investigate the lipid profile, adiponectin, leptin, nitric oxide (NO), and high sensitivity C-reactive protein (hs-CRP) levels in KTR and to compare these parameters with those of the patients with chronic renal failure (CRF), hemodialysis (HD) patients, and healthy controls. Methods: Serum adiponectin and leptin levels were measured by radioimmunoassay; hs-CRP was determined immunoturbidimetrically. Determination of NO was based on the Griess reaction. Results: Compared with the control group, serum NO and adiponectin levels were significantly higher in the KTR, CRF, and HD groups; hs-CRP levels were significantly higher in the KTR and HD groups; leptin levels were significantly higher in the KTR. In addition, serum NO level was significantly higher in the KTR compared to CRF cases. Adiponectin correlated positively with high density lipoprotein-cholesterol in the control and patient groups. A positive correlation was observed between hs-CRP and NO in the KTR and the patients with CRF. Serum adiponectin levels were inversely correlated with hs-CRP and leptin in the HD group. Conclusion: KTR suffer from inflammation and accompanying changes in levels of adipocytokines and NO which contribute to the increased risk of CVD in these patients.